2002
DOI: 10.1128/jcm.40.8.2791-2794.2002
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Gram Staining for Evaluation of the Quality of Cystic Fibrosis Sputum Samples

Abstract: The microscopic examination of Gram-stained sputum specimens is very helpful in the evaluation of patients with community-acquired pneumonia and has also been recommended for use in cystic fibrosis (CF) patients. This study was undertaken to evaluate that recommendation. One hundred one sputum samples from CF patients were cultured for gram-negative bacilli and examined by Gram staining for both sputum adequacy (using the quality [Q] score) and bacterial morphology. Subjective evaluation of adequacy was also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
(10 reference statements)
1
9
0
2
Order By: Relevance
“…Apart from immunocompromised patients, the recovery rate of M. catarrhalis in smokers is high as compared to non-smokers and ex-smokers with underlying AECOPD. This observation concurs with those of previous investigators who have stated that cigarette smoking and tobacco smoke exposure could exacerbate the COPD state [5,[8][9][10] . In line with others, we observed that 1 90% of M. catarrhalis isolates produced ␤ -lactamase [11,12] .…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Apart from immunocompromised patients, the recovery rate of M. catarrhalis in smokers is high as compared to non-smokers and ex-smokers with underlying AECOPD. This observation concurs with those of previous investigators who have stated that cigarette smoking and tobacco smoke exposure could exacerbate the COPD state [5,[8][9][10] . In line with others, we observed that 1 90% of M. catarrhalis isolates produced ␤ -lactamase [11,12] .…”
supporting
confidence: 52%
“…AECOPD patients fulfilled the diagnostic criteria of COPD J44.x according to the 10th edition of the International Classification of Diseases guidelines. Sputum specimens were collected and cultured on 5% sheep blood agar and chocolate agar and incubated in a CO 2 environment for 24-48 h. Based on microscopy, only specimens representative of the lower respiratory tract were used [5] . M. catarrhalis isolates obtained were tested for sensitivity to ␤ -lactam antibiotics, a combination of ␤ -lactam and clavulanic acid, macrolides and quinolones.…”
mentioning
confidence: 99%
“…Culture positive samples were more likely to contain polymorphonuclear cells or bacteria, suggesting that inadequacy of samples may have contributed to negative culture findings. However, gram stain evaluation has been shown to have poor correlation with culture results for CF sputum samples 34. Culture interference by antibiotics is a valid concern in our study, given the high number of patients on antibiotics at the time of admission.…”
Section: Discussionmentioning
confidence: 96%
“…Microscopy was performed on Gramstained smears, and sputum was cultured on 5% horse blood agar and chocolate agar and incubated in CO 2 for 24Á48 h. The isolates were tested for sensitivity to beta-lactams, combination of betalactam and clavulanic acid, macrolides and quinolones. Based on the microscopy, only specimens representative for lower respiratory tract were used [19].…”
Section: Methodsmentioning
confidence: 99%